Transcatheter Intra-Arterial Infusion Combined with Interventional Photothermal Therapy for the Treatment of Hepatocellular Carcinoma - Zhou J (Dove Medical Press, 2020)
Jun Zhou,1 Gonghao Ling,1 Jia Cao,1 Xun Ding,1 Xingnan Liao,1 Meng Wu,2 Xinyu Zhou,3 Haibo Xu,1 QingYun Long1 1Department of Radiology, Zhongnan Hospital of Wuhan University, Wuhan 430071, Hubei, People’s Republic of China; 2Department of Ultrasound, Zhongnan Hospital of Wuhan University, Wuhan 430071, Hubei, People’s Republic of China; 3Department of Radiation and Medical Oncology, Zhongnan Hospital of Wuhan University, Wuhan 430071, Hubei, People’s Republic of ChinaCorrespondence: Haibo Xu; QingYun LongDepartment of Radiology, Zhongnan Hospital of Wuhan University, No. 169 Donghu Road, Wuhan 430071, Hubei, People’s Republic of ChinaTel +86 13545009416; +86 15827339526Email xuhaibo1120@hotmail.com; longqy2005@sina.comBackground: Photothermal therapy (PTT) has great potential application in the treatment of tumors. However, due to the low penetration of near-infrared light (NIR) and the low concentration of nanomaterials in the tumor site, the application of PTT has been limited.Purpose: The objective of this study was to investigate the therapeutic effect of transcatheter intra-arterial infusion of lecithin-modified Bi nanoparticles (Bi-Ln NPs) combined with interventional PTT (IPTT) on hepatocellular carcinoma.Methods: Bi-Ln NPs were prepared by emulsifying the hydrophobic Bi nanoparticles and lecithin, and the photothermal conversion and cytotoxicity of Bi-Ln NPs were then measured by infrared imaging and MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay, respectively. Twenty-four VX2 hepatic carcinoma rabbits were randomly divided into four groups. Rabbits in group A received Bi-Ln NPs by intra-arterial infusion and NIR laser treatment (IA Bi-Ln NPs + Laser), group B received Bi-Ln NPs by intravenous infusion and NIR laser treatment (IV Bi-Ln NPs + Laser), group C received PBS (phosphate buffer saline) via intra-arterial infusion with NIR laser treatment (IA PBS + Laser), group D received PBS via intra-arterial infusion (IA PBS). Transcatheter intra-arterial infusion was conducted by superselective intubation under digital subtraction angiography (DSA) guidance. IPTT was performed by introducing an NIR optical fiber access to the rabbit VX2 hepatic carcinoma under real-time ultrasound guidance. Magnetic resonance imaging (MRI) was performed to evaluate the tumor size. Hematoxylin and eosin (H&E) stain and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) were conducted 7 days after treatment to evaluate the necrosis rate and viability of tumor, respectively.Results: The Bi-Ln NPs have the advantages of good biological compatibility and high photothermal conversion efficiency. Minimally invasive transcatheter intra-arterial infusion can markedly increase the concentration of Bi-Ln NPs in tumor tissues. IPTT can contribute to the significant improvement in the photothermal efficiency of Bi-Ln NPs. Compared to other groups, the group of IA Bi-Ln NPs + Laser showed a significantly higher tumor inhibition rate (TIR) of 93.38 ± 19.57%, a higher tumor necrosis rate of 83.12 ± 8.02%, and a higher apoptosis rate of (43.26 ± 10.65%) after treatment.Conclusion: Transcatheter intra-arterial infusion combined with interventional PTT (IPTT) is safe and effective in eradicating tumor cells and inhibiting tumor growth and may provide a novel and valuable choice for the treatment of hepatocellular carcinoma in the future.Keywords: transcatheter intra-arterial infusion, interventional photothermal therapy, Bi nanoparticles, hepatocellular carcinoma